Prevalence of consumption and nutritional content of breakfast meal among adolescents from the Brazilian National Dietary Survey - Jaqueline L. Pereira; Michelle A. de Castro; Sinead Hopkins; Carolyn Gugger; Regina M. Fisberg; Mauro Fisberg (Brazilian Society of Pediatrics, 2018)
Objective: To estimate the prevalence of breakfast consumption and describe the foods and nutrients consumed at this meal and throughout the day by Brazilian adolescents. Method: A total of 7276 adolescents aged 10-19 years were evaluated in the Brazilian National Dietary Survey 2008-9, a population‐based cross‐sectional study. Individuals' information was collected at home. Dietary data were obtained by two food records. Breakfast was defined as the first eating occasion of the day that occurred between 6 and 9:59 am. Differences between breakfast consumers, occasional consumers, and skippers were tested through Pearson's chi‐squared test or F‐test of regression analysis. Results: Breakfast was consumed by 93% of adolescents and it was associated with age, income, geographic region and household area. The most frequently consumed foods at breakfast were white bread, coffee, butter/margarine, refined cookies and crackers, and whole milk. The mean daily intakes of total energy, sugar, and calcium were higher among occasional consumers and skippers. Breakfast consumers had higher intake of vitamins B12, C, and D. Breakfast contributed more to total intake of calcium, phosphorus, thiamin, riboflavin, and vitamins A, B6, and D (17-32%), trans fat and sodium (about 30%) and less to folate, vitamin C, iron, zinc, and fiber (8-12%) and energy intake (16%). Conclusions: Although the prevalence of breakfast consumption among Brazilian adolescents was high, the overall nutritional quality of this meal is suboptimal, highlighting the need to support adolescents and their families to make more nutrient‐dense food choices. Resumo: Objetivo: Estimar a prevalência de consumo de café da manhã e descrever os alimentos e nutrientes consumidos nessa refeição e durante todo o dia por adolescentes brasileiros. Método: Foram avaliados 7.276 adolescentes entre 10‐19 anos no Inquérito Nacional de Alimentação 2008‐2009, um estudo transversal de base populacional. As informações dos indivíduos foram coletadas nos domicílios. Os dados alimentares foram obtidos por dois registros alimentares. O café da manhã foi definido como a primeira refeição do dia entre 6h e 9h59. As diferenças entre os consumidores de café da manhã, consumidores ocasionais e aqueles que não tomam café da manhã foram testadas por meio do teste de qui‐quadrado ou teste F para análise de regressão. Resultados: O café da manhã foi consumido por 93% dos adolescentes e seu consumo foi associado à idade, renda, região geográfica e área residencial. Os alimentos mais frequentemente consumidos foram pão branco, café, manteiga/margarina, biscoitos e bolachas refinados e leite integral. A ingestão média diária de energia total, açúcar e cálcio foi maior entre os consumidores ocasionais e aqueles que não tomam café da manhã. Aqueles que tomam café da manhã apresentam maior ingestão de vitaminas B12, C e D. O café da manhã contribuiu mais para a ingestão total de cálcio, fósforo, tiamina, riboflavina e vitaminas A, B6 e D (17%‐32%), gordura trans e sódio (cerca de 30%) e menos para a ingestão de ácido fólico, vitamina C, ferro, zinco e fibras (8%‐12%) e energia (16%). Conclusões: Apesar de a prevalência de consumo de café da manhã entre os adolescentes brasileiros ter sido alta, a qualidade nutricional dessa refeição está abaixo do ideal, destaca a necessidade de apoio aos adolescentes e suas famílias para possibilitar a escolha de alimentos mais densos em nutrientes. Keywords: Breakfast, Adolescent, Food intake, Nutritional requirements, Brazil, Palavras‐chave: Café da manhã, Adolescente, Ingestão de alimentos, Necessidades nutricionais, Brasil